POLA PEMANTAUAN & PENGAWASAN TERHADAP PEMBIAYAAN DALAM BANK SYARIAH - Carolina, Anna; Vitram, Khansa Lathifah; Reni, Kok; Anzani, Mayang; Maulina, Mila (STAI Darul Qalam Tangerang, 2024)
To prevent irregularities and facilitate supervision of a financing, the prospective customer must take several procedures, including financing approval procedures, administrative procedures (completing the financing requirements documents) and monitoring procedures. The monitoring stage is something that must be carried out by Islamic banks by directly observing all customer activities until the customer has paid off the financing according to article 2(2) PBI No. 5/7. / PBI / 2003. Preventive supervision is an effort by Islamic banks to secure and ensure financing so that the quality of financing can be maintained properly, this is regulated in Financial Services Authority Regulation No. 42/POJK. 03/2017. The monitoring process can be carried out in various ways, namely on desk monitoring (administrative monitoring of financing), on site monitoring (visiting the customer's business location), and exception monitoring (monitoring of financing under pressure). This monitoring really needs to be done because if there is a failure in the financing sector it can affect the soundness of the bank and the continuity of the business which in this case is caused by problematic financing.